2019
DOI: 10.1161/circinterventions.119.007924
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically Guided Complete Revascularization Versus Selective Stress Echocardiography–Guided Revascularization in Patients With ST-Segment–Elevation Myocardial Infarction and Multivessel Disease

Abstract: Background: Recent trials suggest that complete revascularization in patients with acute ST-segment–elevation myocardial infarction and multivessel disease is associated with better outcomes than infarct-related artery (IRA)–only revascularization. There are different methods to select non-IRA lesions for revascularization procedures. We assessed the clinical outcomes of complete angiographically guided revascularization versus stress echocardiography–guided revascularization in patients with ST-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
8
0
5
Order By: Relevance
“…Como se ha descrito anteriormente 10 , el estudio clínico CROSS-AMI fue un ensayo clínico multicéntrico aleatorizado que comparó una estrategia de revascularización anatómica completa de todas las lesiones coronarias no culpables durante el ingreso inicial (RCom) con una estrategia de revascularización guiada por isquemia detectada mediante ecocardiografía de estrés (RSel) en pacientes con SCACEST y enfermedad multivaso 10 . El Comité de Ética aprobó el estudio, que siguió las directrices de la Declaración de Helsinki (referencia 2010/160) y se registró en ClinicalTrials.gov con el identificador NCT01179126.…”
Section: Diseño Del Estudio Cross-amiunclassified
See 1 more Smart Citation
“…Como se ha descrito anteriormente 10 , el estudio clínico CROSS-AMI fue un ensayo clínico multicéntrico aleatorizado que comparó una estrategia de revascularización anatómica completa de todas las lesiones coronarias no culpables durante el ingreso inicial (RCom) con una estrategia de revascularización guiada por isquemia detectada mediante ecocardiografía de estrés (RSel) en pacientes con SCACEST y enfermedad multivaso 10 . El Comité de Ética aprobó el estudio, que siguió las directrices de la Declaración de Helsinki (referencia 2010/160) y se registró en ClinicalTrials.gov con el identificador NCT01179126.…”
Section: Diseño Del Estudio Cross-amiunclassified
“…El evento principal del estudio original, un combinado de muerte cardiovascular, infarto agudo de miocardio, revascularización coronaria y reingreso por insuficiencia cardiaca, ocurrió en 22 pacientes (14%) asignados a la RCom y 21 (14%) de la rama de RSel (hazard ratio = 0,95; intervalo de confianza del 95% [IC95%], 0,52-1,72; p = 0,85). No hubo diferencias en cuanto al riesgo de cada uno de los componentes individuales del evento principal (tabla 1 del material adicional) 10 .…”
Section: Eventosunclassified
“…Multivessel Disease and ST-Segment Elevation Myocardial Infarction (CROSS-AMI) koje je uspoređivalo angiografijom i stresnom ehokardiografijom vođenu revaskularizaciju u bolesnika primljenih sa STEMI-jem koji su imali leziju koja nije bila uzrok infarkta sa stenozom dijametra >50 % na kvantitativnoj koronarografiji. 49 Istraživanje je prerano zaustavljeno nakon uključivanja 77 % predviđenih bolesnika zbog sporog uključivanja bolesnika (n = 306). Autori su prijavili veću incidenciju revaskularizacije lezija koje nisu uzorkovale infarkt u angiografskoj skupini (80 % nasuprot 22 %).…”
Section: Slični Su Rezultati Nađeni U Istraživanju Complete Revascularization or Stress Echocardiography In Patients Withunclassified
“…Istraživanje LRP pružilo je dokaze utjecaja sastava plaka na ishode, ali nije istražila sinergistički učinak NIRS-a i IVUS-a u predviđanju neželjenih događaja jer tion (CROSS-AMI) study that compared angiography vs. stress echocardiography-guided revascularization in patients admitted with a STEMI that had non-culprit lesions with a diameter stenosis >50% on quantitative coronary angiography. 49 The study was prematurely stopped after enrolling 77% of the patients because of a slow recruitment (n = 306). The authors reported a higher incidence of non-culprit lesion revascularization in the angiography group (88% vs. 22%).…”
Section: Ranjivi Plakovi I Identifikacija Bolesnikamentioning
confidence: 99%
“…SE is frequently used in i) risk stratification of patients with suspected CAD, ii) pre-operative risk assessment, iii) revascularization evaluation, iv) assessment of indications for percutaneous coronary intervention (PCI) and v) CAD/MI of unclear significance as determined by CAG or CT (6,11). A high number of studies have reported on the use of myocardial contrast echocardiography (MCE) perfusion imaging to improve the wall motion sensitivity of SE (12,13). MCE allows for simultaneous evaluation of myocardial perfusion and regional function and has a potential role in viability assessment (6,7).…”
Section: Introductionmentioning
confidence: 99%